Possible involvement of self-defense mechanisms in the preferential vulnerability of the striatum in Huntington's disease - Francelle, Laetitia; Galvan, Laurie; Brouillet, Emmanuel (Frontiers in Cellular Neuroscience, 2014)
HD is caused by a mutation in the huntingtin gene that consists in a CAG repeat expansion translated into an abnormal poly-glutamine (polyQ) tract in the huntingtin (Htt) protein. The most striking neuropathological finding in HD is the atrophy of the striatum. The regional expression of mutant Htt (mHtt) is ubiquitous in the brain and cannot explain by itself the preferential vulnerability of the striatum in HD. mHtt has been shown to produce an early defect in transcription, through direct alteration of the function of key regulators of transcription and in addition, more indirectly, as a result of compensatory responses to cellular stress. In this review, we focus on gene products that are preferentially expressed in the striatum and have down- or up-regulated expression in HD and, as such, may play a crucial role in the susceptibility of the striatum to mHtt. Many of these striatal gene products are for a vast majority down-regulated and more rarely increased in HD. Recent research shows that some of these striatal markers have a pro-survival/neuroprotective role in neurons (e.g. MSK1, A2A and CB1 receptors) whereas others enhance the susceptibility of striatal neurons to mHtt (e.g. Rhes, RGS2, D2 receptors). The down-regulation of these latter proteins may be considered as a potential self-defense mechanism to slow degeneration. For a majority of the striatal gene products that have been identified so far, their function in the striatum is unknown and their modifying effects on mHtt toxicity remain to be experimentally addressed. Focusing on these striatal markers may contribute to a better understanding of HD pathogenesis, and possibly the identification of novel therapeutic targets.